2012
DOI: 10.1124/mol.112.083097
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Metastasis Suppressor, NDRG1, Using Novel Iron Chelators: Regulation of Stress Fiber-Mediated Tumor Cell Migration via Modulation of the ROCK1/pMLC2 Signaling Pathway

Abstract: The iron-regulated metastasis suppressor, N-myc downstreamregulated gene 1 (NDRG1), is up-regulated by cellular iron depletion mediated by iron chelators and can inhibit cancer cell migration. However, the mechanism of how NDRG1 achieves this effect remains unclear. In this study, we implemented established and newly constructed NDRG1 overexpression and knockdown models using the DU145, HT29, and HCT116 cancer cell lines to investigate the molecular basis by which NDRG1 exerts its inhibitory effect on cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
144
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(160 citation statements)
references
References 57 publications
16
144
0
Order By: Relevance
“…We also previously demonstrated that NDRG1 inhibits a number of EGFR downstream pathways, including PI3K, RAS, etc. (6,8,(17)(18)(19), leading to inhibition of cell migration and invasion (4,20). Together, these results indicate that NDRG1 is a highly promising therapeutic target in cancer cells.…”
Section: In the Presence Of Egf Ndrg1 Inhibits Formation Of The Egfrmentioning
confidence: 67%
See 4 more Smart Citations
“…We also previously demonstrated that NDRG1 inhibits a number of EGFR downstream pathways, including PI3K, RAS, etc. (6,8,(17)(18)(19), leading to inhibition of cell migration and invasion (4,20). Together, these results indicate that NDRG1 is a highly promising therapeutic target in cancer cells.…”
Section: In the Presence Of Egf Ndrg1 Inhibits Formation Of The Egfrmentioning
confidence: 67%
“…This occurs due to the ability of these ligands to bind and sequester intracellular iron leading to activation of HIF1␣-dependent and -independent mechanisms (1,24). Furthermore, this response to these agents has been shown to occur in both PANC-1 and HT-29 cells (3,4,20). These agents were also demonstrated to broadly inhibit a number of oncogenic pathways via NDRG1-dependent mechanisms, including TGF-␤, WNT, PI3K, etc.…”
Section: In the Presence Of Egf Ndrg1 Inhibits Formation Of The Egfrmentioning
confidence: 99%
See 3 more Smart Citations